Citizenship for a changing global climate: Learning from New Zealand and Norway. (April 2015) - Hayward, Bronwyn; Selboe, Elin; Plew, Elizabeth
Young citizens under the age of 25 years make up just under half of the world's population. Globally, they face new, interrelated problems of dangerous environmental change, including increasing incidence of severe storms associated with a changing climate, and related new threats to human security. Addressing the complex challenge of climate change will require new understandings of citizen rights and responsibilities. In this context, we were interested in comparing and contrasting how young citizens currently conceive their rights and responsibilities in two high-consumption societies with sharply contrasting democratic contexts: New Zealand's market liberal democracy and the social democratic state of Norway. Discussion reflects on youthful expectations of citizen rights and responsibilities and the implications of their assumptions in a changing climate.